Osteoporoza – obraz kliniczny, czynniki ryzyka i diagnostyka - Tkaczuk-Włach, Joanna; Sobstyl, Małgorzata; Jakiel, Grzegorz (Menopause Review/Przegląd Menopauzalny, 2010)
Osteoporosis is defined as a skeletal disease with low bone mass and micro-architectural deterioration of bone tissue. Osteoporosis is an insidious disease and usually develops for some time before being detected. Usually the first indication of osteoporosis is fracture. Common sites for osteoporotic fracture are hip, spine and wrist. Osteoporosis is categorized as either primary or secondary. The aim of osteoporosis management is to reduce fracture risk. The primary clinical goal is identification of patients at high risk of fracture rather than identification of women or men with osteoporosis. Bone mineral density (BMD) is most commonly measured for information about bone strength but it is only one component of fracture risk. A large number of clinical risk factors for fracture have been identified and can provide information on fracture risk independently of BMD.